STRATEGI PENGEMBAGAN KREATIVITAS ANAK USIA DINI DALAM MENGANYAM DENGAN MEDIA - Ida Bagus Alit Arta Wiguna; Ni Gusti Ayu Nyoman Putriani; Ni Made Arini (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
Weaving activities using origami as a way to develop early childhood creativity and improve children's fine motor development. This study aims to determine the teacher's strategy in developing children's creativity with origami media. This research uses descriptive qualitative method with a case study approach. The results of research on increasing creativity in early childhood using origami media at the Pembina Mataram State Kindergarten have increased but not overall significantly. The results of the research on the obstacles faced by teachers are as follows: 1) origami media is a medium that is quite difficult and takes a long time to be taught to children; 2) when children already feel difficulties they will immediately not conducive. The obstacles faced by children are: children have difficulty inserting origami pieces into the base of origami paper because they are rarely used so children are not used to it. The results of the research efforts that have been carried out by the teacher are that before starting the core learning the teacher always invites children to tell stories and sing so that children feel comfortable and happy to be in class, after being comfortable the teacher starts with core lessons so that children become conducive and children's creativity increases. can be seen through the results done by children.